A high-density lutetium tungsten tellurite glass-ceramics and preparation method thereof

Through high-temperature melt crystallization method and rare earth ion doping technology, high-density purterophenium tungsten tellurate microcrystalline glass was prepared, solving the difficulty and pollution of existing scintillation crystals, and achieving the performance improvement of high luminescence intensity and high mechanical hardness .

CN116462413BActive Publication Date: 2025-02-25JINGGANGSHAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211666632.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-02-25
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

The existing scintillation crystals in the field of high-energy physics have problems such as long growth cycles, complex processes, expensive costs and difficult growth of large-sized single crystals. At the same time, some inorganic scintillation crystals also contain highly toxic chemical elements that are highly polluted by the environment, which limits their long-term develop.

Method used

Through high-temperature melt crystallization method, high-density purterophenium tungsten tellurate microcrystalline glass containing Lu4Te7O20 crystal phase was prepared. Rare earth ion doping technology was used to replace Lu2O3 in the matrix glass component for doping to form high-density and high luminescence Glass with strength and high mechanical hardness.

Benefits of technology

The preparation of high-density (nearly 6.0g/cm3) tungsten tellurite microcrystalline glass is achieved, which improves its luminous intensity and mechanical properties, avoids the risk of using highly toxic chemical elements, and has a relatively simple process and a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116462413B_ABST
    Figure CN116462413B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-density lutetium tungsten tellurite glass-ceramics and a preparation method thereof. The components and their molar percentage ranges of the glass are: Lu2O3: 8-22%, WO3: 8-22%, TeO2: 58-80%, and the remaining components are Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ The rare earth luminescent ions are doped by replacing Lu2O3 in the matrix glass component, and the corresponding concentration range is 0-9mol%. The invention firstly adopts the traditional melt quenching method to prepare the tungsten lutetium tellurate matrix glass, and then performs crystallization treatment by program temperature control to obtain Lu4Te7O 20 Crystalline glass-ceramics. The glass-ceramics prepared by the present invention has the advantages of high density, enhanced hardness, and does not contain highly polluting heavy metals such as Pb and Cd, and is more environmentally friendly, and is suitable for use in high-energy ray detection fields such as X-rays, gamma rays and nuclear medical imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic luminescent materials, and in particular relates to a high-density lutetium tungsten tellurite glass-ceramics and a preparation method thereof. Background Art

[0002] Scintillating materials are optically functional materials that emit visible light after absorbing high-energy rays. In recent years, they have played an increasingly important role in high-energy physics, medical imaging, nuclear physics, industrial flaw detection, and safety testing. There are many types of scintillating materials, which can be divided into inorganic scintillators and organic scintillators according to their chemical composition. In the field of high-energy physics, some well-known commercial inorganic scintillating crystals, such as Bi4Ge3O 12 (BGO), CeF3, PbWO4 (PWO), etc. all have high density characteristics. However, scintillation crystals have disadvantages such as long growth cycle, complex process, high cost, and difficulty in growing large-sized single crystals. In addition, some inorganic scintillation crystals also contain highly toxic chemical elements such as Pb, Cd, and Tl that pollute the environment. These disadvantages and factors have greatly restricted their long-term development.

[0003] Rare earth ion doped scintillating glass and its microcrystalline glass are expected to replace commercial scintillating crystals due to their advantages of easy adjustment of chemical composition, good optical uniformity, easy realization of large size and simple preparation method, thus arousing great interest and attention of scientific researchers. Microcrystalline glass is a new type of optical material obtained by re-crystallization heat treatment of matrix glass. It has the advantages of excellent optical properties of crystals, simple preparation, low cost and stable performance of glass.

[0004] At present, there are few reports on high-density microcrystalline glass, especially in the field of scintillation. For example, the invention patent with publication number CN114455842A, entitled "Precipitation of Bi2GeO5 nanocrystalline high-density bismuth germanate microcrystalline glass and its preparation method", discloses a high-density microcrystalline glass with a density of more than 6g / cm 3 The patent does not involve rare earth ion doping and is limited to possible near-infrared luminescent materials. In the invention patent with publication number CN 105399334A and titled "A scintillating glass-ceramic embedded with GdTaO4 microcrystalline phase and its preparation method", a silicate glass embedded with Mˊ-type GdTaO4 crystal phase is disclosed. Although the density of Mˊ-type GdTaO4 crystal phase is as high as XX, the entire glass-ceramic is rich in SiO2 and Al2O3, and the density data of the glass-ceramic is not given. Therefore, the entire glass preparation temperature is as high as 1650C, and a Pt crucible is required as a container, which is not conducive to the low-cost preparation of glass-ceramic. For example, the invention patent with publication number CN107698165A and titled "A glass-ceramic containing bismuth germanate crystal phase and its preparation method" discloses a glass-ceramic containing Bi4Ge3O12 Crystalline glass-ceramics with a crystalline phase, but the optical transmittance of the glass-ceramics is as low as 5%, which is not conducive to the light output of the scintillating glass-ceramics. In recent years, the maturity and promotion of container-free preparation technology has brought new hope for the preparation of high-density glass-ceramics. For example, the invention patent with publication number CN108264234A and the name "A scintillating glass-ceramic embedded with a microcrystalline phase and its preparation method" discloses a method for preparing transparent scintillating glass-ceramics embedded with a GYAGG:Ce crystalline phase, but the size of the glass-ceramics prepared by container-free technology is difficult to exceed 6mm in diameter, which limits its practical application. Although the reported scintillating glass-ceramics have made certain progress, there are always limitations such as small sample size, low transparency, low density, and limited types of precipitated crystal phases.

[0005] Lu4Te7O 20 The material has a face-centered cubic structure, the crystal phase space group is F, and the theoretical density is as high as 19.188g / cm 3 There are almost no reports on the preparation of such crystals or ceramic materials. 20 Crystalline glass-ceramics have not been reported. This patent discloses the preparation of Lu4Te7O by high temperature melting crystallization method. 20 The preparation method of crystalline phase microcrystalline glass-ceramics has greatly enriched the types of crystalline phases precipitated in microcrystalline glass-ceramics, and also effectively improved the luminescence and mechanical properties of microcrystalline glass-ceramics. Summary of the invention

[0006] In order to solve the above technical problems existing in the prior art, the purpose of the present invention is to provide a high-density lutetium tungsten tellurite glass-ceramics made of the following raw materials, the molar percentage of each raw material is: Lu2O3: 8-22%, WO3: 8-22%, TeO2: 58-80%, and the remaining components are Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ Rare earth luminescent ions such as Lu2O3 are doped by replacing the Lu2O3 in the matrix glass component, and the corresponding concentration range is 0 to 9 mol%.

[0007] The method for preparing the high-density lutetium tungsten tellurite glass-ceramics specifically comprises the following steps:

[0008] Step A—Material calculation and batching: Select the molar percentage of the glass composition above, convert it into the corresponding mass, accurately weigh each raw material, and grind and mix it evenly in an agate mortar;

[0009] Step B—high-temperature melting: pour the glass raw materials ground and mixed uniformly in step A into a corundum crucible, and place it in a high-temperature electric furnace for melting at a melting temperature of 900 to 1150° C. for a melting time of 0.5 to 3 hours;

[0010] Step C—casting and molding: the evenly melted melt obtained in step B is cast into a cast iron mold preheated at 380-500° C. for molding;

[0011] Step D—precision annealing: the glass cast in step C is placed in a muffle furnace for annealing at a temperature of 380 to 500° C. for 2 to 4 hours; then the power supply of the muffle furnace is turned off and the glass is cooled to room temperature;

[0012] Step E—double-sided polishing: Take out the glass in step D, cut, grind, and polish to obtain a lutetium tungsten tellurite glass sample.

[0013] Step F—Crystallization treatment: After the lutetium tungsten tellurite glass obtained in step E is placed in a preset temperature range of 550-685°C for crystallization treatment for 1-8 hours, Lu4Te7O 20 Crystalline phase of lutetium tungsten tellurite glass-ceramics.

[0014] The high-density lutetium tungsten tellurite glass-ceramics of the present invention has a simple preparation process and a density of approximately 6.0 g / cm3. Compared with lutetium tungsten tellurite matrix glass, the high-density lutetium tungsten tellurite glass-ceramics prepared by the present invention has higher luminous intensity and mechanical hardness and other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is Tb of Example 1 3+ Photoluminescence spectrum of high-density gadolinium-doped lutetium-germanate glass;

[0016] Figure 2 is Eu of Example 2 3+ Photoluminescence spectrum of high-density gadolinium-doped lutetium-germanate glass;

[0017] Figure 3 is Eu of Example 3 3+ XRD patterns of high density gadolinium-doped lutetium-germanate glass and its glass-ceramics;

[0018] Figure 4 is Eu of Example 3 3+ Photoluminescence spectra of high-density gadolinium-doped lutetium-germanate glass and its glass-ceramics;

[0019] Figure 5 is Eu of Example 3 3+ Vickers hardness diagram of high density doped gadolinium lutetium germanate glass and its glass-ceramics;

[0020] Figure 6 is Dy of Example 4 3+ Photoluminescence spectrum of high-density gadolinium-doped lutetium-germanate glass. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings.

[0022] The compositions of five specific embodiments of the high-density lutetium tungsten tellurite glass-ceramics of the present invention are shown in Table 1.

[0023] Table 1. Composition of high density lutetium tungsten tellurite glass-ceramics

[0024] Example No. <![CDATA[TeO2]]> <![CDATA[Lu2O3]]> <![CDATA[WO3]]> <![CDATA[Re2O3]]> density Example 1 78 9 10 <![CDATA[3(Tb2O3)]]> 5.874 Example 2 70 12.5 16.5 <![CDATA[1(Eu2O3)]]> 6.459 Example 3 65 14 18 <![CDATA[3(Eu2O3)]]> 6.488 Example 4 62.5 17.5 19 <![CDATA[1(Dy2O3)]]> 6.625 Example 5 60 19 20 <![CDATA[1(Tb2O3)]]> 6.937

[0025] The present invention is further described in detail below with reference to the accompanying drawings.

[0026] Embodiment 1:

[0027] According to the glass composition of 78TeO2~9Lu2O3~10WO3~3Tb2O3 (mol%), weigh 15 grams of the required TeO2, Lu2O3, WO3, Tb2O3 powder raw materials, put them into an agate mortar and grind them thoroughly and mix them evenly. Pour the mixed glass raw materials into a crucible, place it in a 950℃ silicon carbon rod electric furnace to melt for 45 minutes, then quickly pour the glass melt into a cast iron mold preheated at 390℃, and after the glass is formed, transfer it to a 400℃ muffle furnace for annealing for 3.5 hours, and naturally cool it to room temperature to obtain a glass sample.

[0028] In this embodiment, under 378nm excitation, Tb 3+ The photoluminescence spectrum of high density gadolinium-doped lutetium-germanate glass is shown in Figure 1 shown.

[0029] Embodiment 2:

[0030] According to the glass composition of 70TeO2~12.5Lu2O3~16.5WO3~1Eu2O3 (mol%), weigh 15 grams of the required TeO2, Lu2O3, WO3, Eu2O3 powder raw materials, put them into an agate mortar and grind them thoroughly and mix them evenly. Pour the mixed glass raw materials into a crucible, place it in a 980℃ silicon carbon rod electric furnace to melt for 70 minutes, then quickly pour the glass melt into a preheated 420℃ cast iron mold, after the glass is formed, transfer it to a 435℃ muffle furnace for annealing for 3 hours, and naturally cool it to room temperature to obtain a glass sample.

[0031] In this embodiment, under 394nm excitation, Eu 3+ The photoluminescence spectrum of high density gadolinium-doped lutetium-germanate glass is shown in Figure 2 shown.

[0032] Embodiment 3:

[0033] According to the glass composition of 65TeO2~14Lu2O3~18WO3~3Eu2O3 (mol%), weigh 15 grams of the required TeO2, Lu2O3, WO3, and Eu2O3 powder raw materials, put them into an agate mortar and grind them thoroughly and mix them evenly. Pour the mixed glass raw materials into a crucible, place them in a 1050℃ silicon carbon rod electric furnace to melt for 75 minutes, then quickly pour the glass melt into a cast iron mold preheated at 440℃, and after the glass is formed, transfer it to a 480℃ muffle furnace for annealing for 3 hours, and naturally cool it to room temperature to obtain a glass sample. After the high-density lutetium tungsten tellurite glass prepared in this embodiment is placed in a preset temperature of 600, 625, 650 and 675℃ for crystallization for 2 hours, Lu4Te7O 20 Crystalline lutetium tungsten tellurite glass-ceramic, cut and double-sided polished for performance testing.

[0034] In this embodiment, the XRD spectra of the high-density gadolinium lutetium germanate glass and its glass-ceramics are compared as follows: Figure 1 As shown in the figure, the mantou peak of high-density gadolinium lutetium germanate glass indicates its amorphous nature. The glass was crystallized at 600, 625, 650 and 675℃ for 2 hours, and the peaks of Lu4Te7O 20 The XRD peaks are consistent with the crystal phase, and as the crystallization temperature increases, the corresponding diffraction peak intensity becomes stronger, indicating that Lu4Te7O is precipitated. 20 The better the crystal quality.

[0035] In this embodiment, the Vickers hardness test results of the high-density gadolinium lutetium germanate glass and its glass-ceramics are as follows: Figure 3 As shown in the figure, the Vickers hardness of the high-density gadolinium lutetium germanate glass is 432.8. The Vickers hardness of the microcrystalline glass obtained after crystallization at 600, 625, 650 and 675°C for 2 hours is 469.5, 497.9, 495.2 and 522.1 respectively, and its mechanical properties are improved by 22.63%.

[0036] Embodiment 4:

[0037] According to the glass composition of 62.5TeO2~17.5Lu2O3~19WO3~1Dy2O3 (mol%), weigh 15 grams of the required TeO2, Lu2O3, WO3, and Dy2O3 powder raw materials, put them into an agate mortar and grind them thoroughly and mix them evenly. Pour the mixed glass raw materials into a crucible, place it in a 1050℃ silicon carbon rod electric furnace to melt for 75 minutes, then quickly pour the glass melt into a cast iron mold preheated at 450℃, and after the glass is formed, transfer it to a 480℃ muffle furnace for annealing for 3 hours, and naturally cool it to room temperature to obtain a glass sample.

[0038] In this embodiment, under 341nm excitation, Dy 3+ The photoluminescence spectrum of high density gadolinium-doped lutetium-germanate glass is shown in Figure 6 shown.

[0039] Embodiment 5:

[0040] According to the composition: 60TeO2~19Lu2O3~20WO3~1Tb2O3 (mol%), weigh 15 grams of the required TeO2, Lu2O3, WO3, Tb2O3 powder raw materials, put them into an agate mortar and grind them thoroughly and mix them evenly. Pour the mixed glass raw materials into a crucible, place it in a silicon carbon rod electric furnace at 1130℃ and melt it for 150 minutes, then quickly pour the glass melt into a cast iron mold preheated at 470℃, and after the glass is formed, transfer it to a muffle furnace at 490℃ for annealing for 2 hours, and naturally cool it to room temperature to obtain a glass sample.

[0041] In this example, the Tb 3+ Photoluminescence spectrum of high-density gadolinium-doped lutetium-germanate glass.

[0042] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.

Claims

1. A high-density lutetium tungsten tellurite glass-ceramics, characterized in that: The components and their molar percentages of the high-density lutetium tungsten tellurite glass-ceramics are: Lu2O3: 12-22%, WO3: 8-22%, TeO2: 58-80%, and the remaining components are Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ The rare earth luminescent ions are doped by replacing Lu2O3 in the matrix glass component, and the corresponding concentration range is 0-9 mol%. The high-density lutetium tungsten tellurite glass-ceramics is prepared by the following steps: Step A—Material calculation and batching: Select the molar percentage of the glass composition above, convert it into the corresponding mass, accurately weigh each raw material, and grind and mix it evenly in an agate mortar; Step B—high-temperature melting: pour the glass raw materials ground and mixed uniformly in step A into a corundum crucible, and melt them in a high-temperature electric furnace at a melting temperature of 1050-1150° C. for 30-90 minutes; Step C—casting and molding: the evenly melted melt obtained in step B is cast into a cast iron mold preheated at 380-500°C for molding; Step D—precision annealing: Place the glass cast in step C in a muffle furnace for annealing at a temperature of 380-500°C for 2-4 hours; then turn off the power of the muffle furnace and cool it to room temperature; Step E—double-sided polishing: taking out the glass in step D, cutting, grinding, and polishing to obtain a lutetium tungsten tellurite glass sample; Step F—Crystallization treatment: After the lutetium tungsten tellurite glass obtained in step E is placed in a preset temperature range of 550-685°C for crystallization treatment for 1-8 hours, Lu4Te7O 20 Crystalline phase of lutetium tungsten tellurite glass-ceramics.

2. The high-density lutetium tungsten tellurite glass-ceramics according to claim 1, characterized in that: The glass formula is: WO3: 13~19%, Lu2O3: 14~18%, TeO2: 61~73%, and the rest is Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ Rare earth luminescent ions are doped by replacing Lu2O3 in the matrix glass component, and the corresponding concentration range is 0.5~6 mol%.

3. The high-density lutetium tungsten tellurite glass-ceramics according to claim 1, characterized in that: The glass formula is: WO3: 11~17%, Lu2O3: 12~16%, TeO2: 63~70%, and the rest is Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ Rare earth luminescent ions are doped by replacing Lu2O3 in the matrix glass component, and the corresponding concentration range is 1~5 mol%.

4. The high-density lutetium tungsten tellurite glass-ceramics according to claim 1, characterized in that: The glass formula is: WO3: 10~16%, Lu2O3: 15~17%, TeO2: 64~68%, and the remaining components are Dy 3+ ,Eu 3+ , Tb 3+ and Sm 3+ Rare earth luminescent ions are doped by replacing Lu2O3 in the matrix glass component, and the corresponding concentration range is 1.5~4 mol%.

5. The high-density lutetium tungsten tellurite glass-ceramics according to claim 3, characterized in that: The luminescence intensity is increased by 170.6% compared with that of lutetium tungstate tellurite matrix glass.

6. The high-density lutetium tungsten tellurite glass-ceramics according to claim 3, characterized in that: The Vickers hardness of the microcrystalline glass is 22.63% higher than that of the lutetium tungsten tellurite matrix glass, and the Vickers hardness of the microcrystalline glass reaches up to 522.1.

Citation Information

Patent Citations

  • Scintillation microcrystalline glass embedded with GdTaO4 microcrystalline phase and preparation method thereof

    CN105399334A

  • Glass-ceramic containing a bismuth germanate crystal phase, and preparation method thereof

    CN107698165A

  • Scintillation crystallized glass embedded with GYAGG: Ce microcrystalline phase and preparation method thereof

    CN108264234A

  • Precipitated Bi2GeO5 nanocrystal high-density bismuth germanate microcrystalline glass and preparation method thereof

    CN114455842A

  • High density tellurate scintillation glass and preparation method thereof

    CN110451795A